Effects of plant nutrient acquisition strategies on biomass allocation patterns in wetlands along successional sequences in the semi-arid upper Yellow River basin - Wang, Xuan; Wang, Le; Li, Weimin; Li, Yifan; An, Yu; Wu, Haitao; Guo, Yue (Frontiers in Plant Science, 2024)
The ecological environment of wetlands in semi-arid regions has deteriorated and vegetation succession has accelerated due to climate warming-induced aridification and human interference. The nutrient acquisition strategies and biomass allocation patterns reflect plant growth strategies in response to environmental changes. However, the impact of nutrient acquisition strategies on biomass allocation in successional vegetation remains unclear. We investigated 87 plant communities from 13 wetland sites in the semi-arid upper Yellow River basin. These communities were divided into three successional sequences of herbaceous community (HC), herbaceous-shrub mixed community (HSC), and shrub community (SC). The nutrient composition of stems and leaves, as well as the biomass distribution above and belowground, were investigated. Results revealed that aboveground biomass increased with succession while belowground biomass decreased. Specifically, SC exhibited the highest stem biomass of 1194.53 g m-2, while HC had the highest belowground biomass of 2054.37 g m-2. Additionally, a significant positive correlation was observed between leaf and stem biomasses in both HC and SC. The nitrogen (N) and phosphorus (P) contents within aboveground parts displayed an evident upward trend along succession sequence. The highest N and P contents were found in SC followed by HSC, and lowest in HC. Stem N was negatively correlated with stem, leaf, and belowground biomass, but positively correlated with root-shoot ratio. Leaf P displayed positive correlations with aboveground biomass while showing negative correlations with belowground biomass and root-shoot ratio. The ratios of C:N, C:P, and N:P in stem and leaf exhibited positive correlations with belowground biomass. The random forest model further demonstrated that stem N and leaf P exerted significant effects on aboveground biomass, while leaf P, stem N and P, as well as leaf C:P ratios, had significant effects on belowground component. Additionally, the root-shoot ratio was significantly exerted by leaf P, leaf C:P ratio, and stem N, P, and C:P ratio. Therefore, the aboveground and belowground biomasses exhibited asynchronisms across successional sequences, while plant nutrient acquisition strategies, involving nutrient levels and stoichiometric ratios, determined biomass allocation pattern. This study offers valuable insights for assessing vegetation adaptability and formulating restoration plans in the semi-arid upper Yellow River basin.